2007
DOI: 10.1158/0008-5472.can-06-3505
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β2 Negatively Regulates the Transactivation of Estrogen Receptor α in Human Breast Cancer Cells

Abstract: Estrogens, by binding to and activating two estrogen receptors (ERA and ERB), are critically involved in the development of the mammary gland and breast cancer. An isoform of ERB, ERB2 (also called ERBcx), with an altered COOH-terminal region, is coexpressed with ERA in many human breast cancers. In this study, we generated a stable cell line from MCF7 breast cancer cells expressing an inducible version of ERB2, along with endogenous ERA, and examined the effects of ERB2 on the ERA protein levels and function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 44 publications
4
112
0
4
Order By: Relevance
“…qPCR-Total RNA was extracted, reverse transcribed, and subjected to real-time qPCR using gene-specific primers, as previously described (18). The expression of genes was normalized to the expression of ␤-glucuronidase and 36B4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qPCR-Total RNA was extracted, reverse transcribed, and subjected to real-time qPCR using gene-specific primers, as previously described (18). The expression of genes was normalized to the expression of ␤-glucuronidase and 36B4.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP and ChIP-Seq-ChIP and ChIP-Seq were performed as previously described (18,19). The antibodies used were as follows: anti-c-Jun (H-79) and normal rabbit IgG from Santa Cruz Biotechnology, anti-p65 (ab7970) and anti-p50 (ab7971) from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…MCF-7 tet-off ER␤ cells were seeded in 150-mm tissue culture plates and grown in the presence (ϩTet; ϪER␤) or absence (ϪTet; ϩER␤) of tetracycline, respectively, for 18 h. The total cell extracts were prepared as described in ref. 22. Aliquots corresponding to 100 g of protein were separated by SDS/PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Total cell extracts from MCF7 tet-off ER␤ cells were incubated with AP1A, AP2A, and LBD antibodies, followed by immunoprecipitation as described in ref. 22. Precipitated fractions and supernatant were transferred to nitrocellulose membrane and visualized by using the anti-Flag M5 monoclonal antibody (Sigma) or the anti-ER␤ chicken polyclonal antibody Ab14021 (Abcam, Cambridge MA).…”
Section: Methodsmentioning
confidence: 99%
“…The potential role of ER beta remains unknown. It has been clearly demonstrated that two ER beta isoforms (splice variants ER beta 1 and ER beta 2) have anti-proliferative functions when introduced into ER alpha-positive breast cancer cells, and ER beta 2 negatively regulates the transactivation of estrogen receptor alpha in MCF-7 cancer cells [40]. This is either by inducing proteasome-dependent degradation of ER alpha or repressing ER alpha-mediated transcriptional activity when co-expressed with ER alpha [22].…”
Section: Discussionmentioning
confidence: 99%